Entre terços e palanques: ativismos de deputadas católicas antifeministas na Câmara Federal - Tesser, Tabata Pastore (2022)
This dissertation examines the institutional activism of two congresswomen, Carla Zambelli (PSL-SP) and Chris Tonietto (PSL-RJ), catholics, self-identified anti-feminists, who were elected for the House of Representatives for its 56a legislature (2019-2023). Focusing on the study of western contemporary anti-feminisms (Bonet-Marti, 2020), it managed to identify how their religious links were articulated in an anti-gender parliamentary agenda. Applying the cyberethnographic method, this research has examined these congresswomen’s posts on social media – Facebook and Instagram. The selection of data was based on thematic criteria concerning anti-gender agenda, and it was possible to note a potential movement of catholic neoconservative groups in strengthening anti-feminist candidacies. With the election of Jair Bolsonaro for president, ultra-conservative catholic groups, with the candidacies of Carla Zambelli and Chris Tonietto, update of the catholic anti-gender repertoire through the intensive use of social media. Identifying the similarities and differences between these congresswomen’s activism, it was possible to identify the central role that the debate over Education Plans played in their path. In relation to the catholic right’s spectrum, it was possible to notice that these anti-feminist congresswomen, guided by a neoconservative religiosity, destined parliamentary amendments in the financing of State policies in order to institutionalize the expression ‘gender ideology’